1998
DOI: 10.1523/jneurosci.18-06-02174.1998
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Tetrodotoxin-Resistant Sodium Channel PN3 in Rat Sensory Neurons in Normal and Neuropathic Conditions

Abstract: The novel sodium channel PN3/alpha-SNS, which was cloned from a rat dorsal root ganglion (DRG) cDNA library, is expressed predominantly in small sensory neurons and may contribute to the tetrodotoxin-resistant (TTXR) sodium current that is believed to be associated with central sensitization in chronic neuropathic pain states. To assess further the role of PN3, we have used electrophysiological, in situ hybridization and immunohistochemical methods to monitor changes in TTXR sodium current and the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
169
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(195 citation statements)
references
References 58 publications
24
169
0
1
Order By: Relevance
“…7) could result from the effect of cyclic GMP on TTX-R I Na rather than K ATP . However, TTX-R sodium channels are expressed in ∼80% of the small diameter sensory neurons (Novakovic et al 1998;Dib-Hajj et al 1998). If the actions of cyclic GMP were on TTX-R I Na only, then we would have expected to encounter ∼80% of the neurons to be sensitive to the inhibitory effects of cyclic GMP whereas we found that the sensitization produced by PGE 2 was reversed by 8-Br cyclic GMP in ∼50% of the small to medium diameter neurons (11 of 21).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…7) could result from the effect of cyclic GMP on TTX-R I Na rather than K ATP . However, TTX-R sodium channels are expressed in ∼80% of the small diameter sensory neurons (Novakovic et al 1998;Dib-Hajj et al 1998). If the actions of cyclic GMP were on TTX-R I Na only, then we would have expected to encounter ∼80% of the neurons to be sensitive to the inhibitory effects of cyclic GMP whereas we found that the sensitization produced by PGE 2 was reversed by 8-Br cyclic GMP in ∼50% of the small to medium diameter neurons (11 of 21).…”
Section: Discussionmentioning
confidence: 70%
“…K ATP channels, originally identified in cardiac myocytes (Noma 1983), are also present in the central nervous system (Amoroso et al 1990;Murphy and Greenfield 1991;Li and Henry 1992;Ohno-Shosaku and Yamamoto 1992). The K ATP channel is an octomeric complex composed of either the Kir6.1 or Kir6.2 channel subunits and sulphonylurea regulatory subunits (SUR) (Inagaki et al 1996;Aguilar-Bryan et al 1998;Ashcroft and Gribble 1998;Babenko et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The number of ATF3-immunoreactive (IR) neurons and total neurons were counted at 4009 magnification using a counting grid. DRG neurons were classified as small (\700 lm 2 ) and large ([700 lm 2 ) according to the measured cross-sectional area [13,14]. Positive or negative staining was blinded and observed by three orthopedic hand surgeons.…”
Section: Immunohistochemistry For Atf3 (A Marker Of Drg Neuron Activamentioning
confidence: 99%
“…The development of hyperalgesia and allodynia in nerve ligation models is reduced with Na v 1.8 antisense treatment (Porreca et al, 1999;Lai et al, 2002;Joshi et al, 2006), while ectopic firing of neurons is related to Na v 1.8 protein expression (Novakovic et al, 1998;Gold et al, 2003). Evidence of a direct role of Na v 1.9 in the development of thermal and mechanical hyperalgesia is lacking in rats with neuropathic pain states (Porecca et al, 1999;Priest et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Reported alterations in the expression of both Na v 1.8 and Na v 1.9 in response to chronic constriction injury (CCI) are conflicting (Novakovic et al, 1998;Dib-Hajj et al, 1999;Decosterd et al, 2002), and the channels respond differently to inflammation (Tanaka et al, 1998;Black et al, 2004;Gould et al, 2004). This may be due to the complexity of the CCI model which produces preferential axotomy of large sized DRG neurons and exposure of the remaining intact axons to an inflammatory environment (Bennett and Xie, 1988;Kajander and Bennett, 1992) with increased levels of nerve growth factor (NGF) that increase injury-induced expression of these channels Fjell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%